Implementation of the Disaster Risk Reduction Program in Japan as an Effort for Disaster Risk Reduction in Indonesia - Muhammad Afif Al Fayed; Syamsul Maarif; Syamsunasir Syamsunasir; Pujo Widodo; Kusuma Kusuma; Muhammad Ihsan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The natural disasters that occurred in Japan have caused losses both financially and in terms of casualties. Based on data from the Japanese government, the total losses experienced by the country from 1980 to 2010 amounted to US$ 208,230,800. Meanwhile, the number of recorded fatalities was 8,568 people, with an average of 276 fatalities per year due to natural disasters in Japan. This study aims to focus on the development of a disaster information system to reduce disaster risk in Japan which can also be implemented in Indonesia. The research method used in this study is a qualitative approach. In this approach, researchers use descriptive methods to collect data. This approach was chosen because this research was conducted during an Overseas Work Lecture through a Video Conference from Japan on May 30, 2023. The conclusions from this study indicate that the Japanese government has changed its approach to natural disasters and prioritized disaster risk reduction (DRR) programs. They focus on better regional planning, building earthquake-resistant buildings, and raising community awareness. In addition, the disaster management system in Japan involves various government ministries and agencies working together in planning, implementing, and supervising disaster management operations. The Japanese government has a strong commitment to the DRR program and regards investment in disaster risk reduction as an important measure to protect the country's life and economy. Through improving urban planning, strict construction regulations, disaster education, and active community participation, Japan is trying to live side by side with disasters and has strong resilience against these threats.